2013
DOI: 10.24840/2183-0606_001.001_0009
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge creation in small building and construction firms

Abstract: Studies on knowledge creation are limited in general, and there is a particular shortage of research on the topic in small and medium-sized enterprises (SMEs). Given the importance of SMEs for the economy and the vital role of knowledge creation in innovation, this situation is unsatisfactory. Accordingly, the purpose of our study is to increase our understanding of how SMEs create new knowledge. Data are obtained through semi-structured interviews with ten managing directors of German SMEs operating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 0 publications
1
17
1
1
Order By: Relevance
“…high-technology firms, [120]). Additionally, among the highly ranked OL processes, professional service firm-related, and consultants activities, and external training underline the relevance of informed external source in KC and KT processes, in alignment with specific literature focused on construction SMEs [121]. However, the scarce use of other types of external sources and related interorganizational KT processes, -such as partners in network contracts, and collaborative R&D projects that present the lowest values, -hihglight a clear preference of "neutral" source of knowledge, in contrast with partner-based collaborative solutions.…”
Section: Source: Authors Elaborationsupporting
confidence: 53%
“…high-technology firms, [120]). Additionally, among the highly ranked OL processes, professional service firm-related, and consultants activities, and external training underline the relevance of informed external source in KC and KT processes, in alignment with specific literature focused on construction SMEs [121]. However, the scarce use of other types of external sources and related interorganizational KT processes, -such as partners in network contracts, and collaborative R&D projects that present the lowest values, -hihglight a clear preference of "neutral" source of knowledge, in contrast with partner-based collaborative solutions.…”
Section: Source: Authors Elaborationsupporting
confidence: 53%
“…This aspect appears to underline that OL processes are not extensively activated (without a specific stimulus from the external environment), in contrast with other organizations, which usually invest in innovations and learning processes to maintain competitive advantages over competitors (e.g., high-technology firms, [121]). Additionally, among the highly ranked OL processes, professional service firm-related and consultants' activities, and external training underline the relevance of informed external source in KC and KT processes, in alignment with specific literature focused on construction SMEs [122]. However, the scarce use of other types of external sources and related interorganizational KT processes-such as partners in network contracts, and collaborative R&D projects that present the lowest values-highlight a clear preference of "neutral" source of knowledge, in contrast with partner-based collaborative solutions.…”
Section: Discussionmentioning
confidence: 52%
“…For example, a case study from Singapore showed that the SME owner was the main driver of knowledge sourcing and creation and the knowledge creation processes rested overall on the owner's innovativeness and creativity (Wee and Chua, 2013). A study by Durst et al (2013) on knowledge creation activities in German SMEs showed the influence of external knowledge sources. Even though the managing directors take advantage of different external knowledge sources, they seem to place the main emphasis on informed knowledge sources.…”
Section: Knowledge Creation In Smesmentioning
confidence: 99%